Escherichia coli bacteraemia in pregnant women is life‐threatening for foetuses. (11th August 2014) - Surgers, L.; Bleibtreu, A.; Burdet, C.; Clermont, O.; Laouénan, C.; Lefort, A.; Mentré, F.; Carbonne, B.; Bingen, E.; Meynard, J.‐L.; Denamur, E.; Grobusch, M.; et al.
Abstract In order to improve knowledge on Escherichia coli bacteraemia during pregnancy, we studied clinical data and performed molecular characterization of strains for 29 E. coli bacteraemia occurring in pregnant women. Bacteraemia mostly occurred in the third trimester of pregnancy (45%) and was community‐acquired (79%). Portals of entry were urinary (55%) and genital (45%). E. coli strains belonged mainly to phylogroups B2 (72%) and D (17%). Four clonal lineages (i.e. sequence type complex (STc) 73, STc95, STc12 and STc69) represented 65% of the strains. The strains exhibited a high number of virulence factor coding genes (10 (3–16)). Six foetuses died (27%), five of them due to bacteraemia of genital origin (83%). Foetal deaths occurred despite adequate antibiotic regimens. Strains associated with foetal mortality had fewer virulence factors (8 (6–10)) than strains involved in no foetal mortality (11 (4–12)) (p 0.02). When comparing E. coli strains involved in bacteraemia with a urinary portal of entry in non‐immunocompromised pregnant vs. non‐immunocompromised non‐pregnant women from the COLIBAFI study, there was no significant difference of phylogroups and virulence factor coding genes. These results show that E. coli bacteraemia in pregnant women involve few highly virulent clones but that severity, represented by foetal death, is mainly related to bacteraemia of genital origin.